STUDENTS LEARNING CENTER STRATEGY BASED ON E-LEARNING AND BLOGS - Leon Andretti Abdillah (Prosiding SNST Fakultas Teknik, 2013)
Education is the main infrastructure for promoting a nation and increasing their competitiveness in globalization era that involves the use of information technology (IT). This paper has goal to expand the alternative for learning strategy based on IT for final year students that will conduct a research for their final report. The final year students are expected have the ability to learn independently to manage the needness of their learning supply. In this paper, the author will discuss how to use the e-learning media and blogs to manage the independently learning environment or self-learning. E-learning offers the flexibilities in term of time and place in supporting the learning activities as well as a media for faculty/lecturer to disseminate learning materials. While the blog has been a free medium for the publication of variety contents, including academic contents. In this papaer, author suggests some the institutions regulations, lecturers roles, and students participations are involve in set the learning environment based on e-learning and blog. These activities able to support students in learning independently or self-learning. Keywords: student learning center, e-learning, blog, IT-based learning